Benefits of Morinda citrifolia L. Fruit Extract on Methotrexate Induced Mitochondrial Toxicity – An In Vivo Study in Rat Liver Mitochondria.: Life Sciences-Biotechnology for Prospective Medical Science - Bhakti, Mhatre; Thankamani, Marar (International Journal of Life Science and Pharma Research, 2021)
Mitochondrial dysfunction has been implicated in the etiology of many drug-induced toxicities. Methotrexate (MTX), an antimetabolite and one of the folic acid antagonists, has widely been used to treat a variety of disorders such as cancer and several autoimmune disorders. It induces oxidative stress which results in many of its ill effects on different target and non-target organs, altering different metabolic pathways and interfering mitochondrial bioenergetics. Here, in our study, we have assessed the toxicity of methotrexate on rat liver mitochondria and its modulation by Morinda citrifolia L. (Noni) fruit extract. MTX significantly affects mitochondrial function, and activity of important mitochondrial enzymes such as Succinate dehydrogenase (SDH), Malate dehydrogenase (MDH) and NADH dehydrogenase. Reduced Cytochrome C – oxidase activity and Reduced glutathione (GSH) levels in MTX treated group (p<0.001) was also observed. An increase in the activity of calcium dependent ATPase (Ca2+ dependent ATPase) was observed along with increase in lipid peroxidation (lpx), and significant decrease in mitochondrial protein in MTX treated groups. Liver mitochondria of animals administered with Noni extract did not show any toxicity and combination of aqueous Noni fruit extract and methotrexate showed amelioration of toxicity as compared to methotrexate alone. Our study suggests that Noni can have significant protective effect on liver injury induced by MTX. Nutraceutical supplement like antioxidants found in edible plants such as Noni may be a safe and effective way of alleviating the liver toxicity. Hence, we propose that combination of Noni and methotrexate can be potentially safer combination in cancer therapy.